2021
DOI: 10.1111/psyp.13989
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in facial emotional valence processing in older people with subjective memory complaints: Behavioral and electrophysiological evidence

Abstract: Subjective memory complaints (SMCs), which occur in the absence of clinical memory deficits, may precede mild cognitive impairment (MCI) or Alzheimer's disease (AD). Some studies have reported a deficit in facial emotion processing in people with MCI or AD. However, it is unclear whether this deficit is also present in older people with SMCs. The present study used behavioral measurements and event-related potentials (ERPs) to investigate the facial emotion processing of 41 older people with SMCs and 38 withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…It is worth noting that cut-off points and categorical distinctions are used in clinical procedures and may be helpful to neuropsychologists using this questionnaire. Partial results from the older subsample have been previously reported (Garrido-Chaves et al, 2021;Perez et al, 2021).…”
Section: Participantsmentioning
confidence: 86%
“…It is worth noting that cut-off points and categorical distinctions are used in clinical procedures and may be helpful to neuropsychologists using this questionnaire. Partial results from the older subsample have been previously reported (Garrido-Chaves et al, 2021;Perez et al, 2021).…”
Section: Participantsmentioning
confidence: 86%
“…The N170 component, associated with face processing, has been investigated in two studies [ 46 , 47 ]. Lazarou et al [ 46 ] found that the N170 amplitude was reduced in SCD patients compared to controls, with a pattern similar to MCI and AD patients.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that face processing may be affected in the early stages of cognitive decline. However, Perez et al [ 47 ] found only significant differences in N170 amplitude or latency between male patients with SCD and male controls. This discrepancy could be due to methodological differences, such as using different emotional valence stimuli.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, individuals with AD display impaired identification of negative facial emotions, inconsistent emotional memory benefit ( Brueckner and Moritz, 2009 ; Klein-Koerkamp et al, 2012 ; Mistridis et al, 2013 ; Cárdenas et al, 2021 ), and inconsistent positivity effect ( Goodkind et al, 2015 ; Zhang et al, 2015 ). People with MCI exhibit impaired negative emotion recognition in people with MCI ( Elferink et al, 2015 ; Morellini et al, 2022 ); and those with SCD show altered facial emotion processing( Perez et al, 2022 ) and emotion dysregulation ( Mah et al, 2021 ). Further, anxiety represents a risk factor of cognitive decline in the elderly ( Pietrzak et al, 2012 ; Santabárbara et al, 2020 ; Gracia-García et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%